THERMORADIOTHERAPY IN COMBINED MODALITY TREATMENT FOR RECTAL CANCER (LITERATURE REVIEW) - D. A. Starodubtseva; Zh. A. Startseva; S. G. Afanasyev; A. Yu. Dobrodeev (Сибирский онкологический журнал, 2018)
Preservation of the rectal sphincter during surgery for rectal cancer is necessary in order to maintain control of bowel function. For this purpose, novel approaches for combining sphincter-saving surgeries with neoadjuvant radiotherapy regimens are extensively developed. There are active discussions on the effectiveness of radiosensitization with the inclusion of chemical and physical components, one of which is local hyperthermia. This article reviews the worldwide experience in treating rectal cancer patients using local hyperthermia combined with radiation therapy. A wide variety of methods, as well as facilities for the procedure, is discussed. It should be noted that the selection of patients with rectal cancer for thermochemoradiotherapy and the choice of optimal irradiation volume remain a challenge.